2017
DOI: 10.1097/aog.0000000000002094
|View full text |Cite
|
Sign up to set email alerts
|

A Shared Decision-Making Intervention to Guide Opioid Prescribing After Cesarean Delivery

Abstract: Objective To assess whether a shared decision-making intervention decreases the quantity of oxycodone tablets prescribed after cesarean delivery. Technique A tablet computer-based decision aid formed the basis of a shared decision-making session to guide opioid prescribing after cesarean delivery. Women first received information on typical trajectories of pain resolution and expected opioid use after cesarean delivery, and then chose the number of tablets of oxycodone 5mg they would be prescribed, up to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 9 publications
2
114
1
Order By: Relevance
“…Given these findings, there is a need to develop and test approaches to better align the amount of opioid medication that is prescribed with what women require. Strategies that have demonstrated promise in this regard include the use of shared decision-making (in which women select the quantity of opioids they want to be prescribed up to a defined limit) 48,49 and individualized prescriptions based on inpatient opioid use. 50 Given the risks and adverse side-effect profile of opioids, some have questioned whether oral opioids should be prescribed routinely for all women after cesarean delivery.…”
Section: Pain Management After Cesarean Delivery Among Opioid-naïve Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these findings, there is a need to develop and test approaches to better align the amount of opioid medication that is prescribed with what women require. Strategies that have demonstrated promise in this regard include the use of shared decision-making (in which women select the quantity of opioids they want to be prescribed up to a defined limit) 48,49 and individualized prescriptions based on inpatient opioid use. 50 Given the risks and adverse side-effect profile of opioids, some have questioned whether oral opioids should be prescribed routinely for all women after cesarean delivery.…”
Section: Pain Management After Cesarean Delivery Among Opioid-naïve Wmentioning
confidence: 99%
“…Rather than prescribing the same quantity of opioids for all women after cesarean delivery, women should be allowed to choose to be prescribed a smaller amount. 48 Pain management among opioid-dependent women Women with opioid dependence in pregnancy are a heterogeneous group. Women with this diagnosis may have chronic pain that is treated with opioids throughout pregnancy, an OUD treated with MAT (buprenorphine or methadone), or an untreated OUD that results in the use of unprescribed or illicit opioids.…”
Section: Pain Management After Cesarean Delivery Among Opioid-naïve Wmentioning
confidence: 99%
“…For cesarean delivery, there is a large variation in opioid prescription and use, 27,28 and shared-decision making strategies have been shown to decrease opioid use. 29 Demonstrating optimal pain management strategies may offer additional benefit in reducing or eliminating postdischarge opioid use. Third, in the population of women with opioid abuse and dependence among whom opioid exposure may be least desirable, overall hospital opioid administration correlated highly with the administration of opioids to women with these diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several studies have demonstrated SDM's benefits in the context of opioid prescribing. SDM can reduce opioid use 6 and increase physician satisfaction in prescribing opioids for patients with chronic pain. 7 Moreover, the finding that patients and clinicians offer conflicting narratives about chronic opioid therapy underscores the special need for SDM among these patients.…”
Section: More Optionsmentioning
confidence: 99%
“…Implementing patient-provider agreements to define patients' roles and responsibilities while using opioids has been shown to be helpful in presenting risks and benefits and in making decisions about treatment. 19 These and other patient-centered approaches improve patient outcomes and satisfaction, 6,7,8 and, ideally, the administrative and logistical burdens imposed by the new laws would not prevent clinicians from engaging in SDM. However, because these burdens exacerbate time constraints within which physicians already work, they could threaten the patientphysician therapeutic alliance, which needs time and care to build and maintain.…”
Section: Opioid Start Talking Form and Shared Decision Makingmentioning
confidence: 99%